Facilitators and barriers for the implementation of a transmural fall-prevention care pathway for older adults in the emergency department. - W M Charmant; B A M Snoeker; H P J van Hout; I N Nauta; F Boonstra; E Geleijn; C Veenhof; P W B Nanayakkara (PLoS ONE)
Background Older adults at the emergency department (ED) with fall-related injuries are at risk of repeated falls. National guidelines state that the ED is responsible for initiating fall preventive care. A transmural fall-prevention care pathway (TFCP) at the ED can guide patients to tailored interventions. In this study, we investigated the facilitators and barriers for the implementation of the TFCP for older adults following a fall-related ED visit from the perspectives of patients and healthcare professionals. Methods In this qualitative study, we used semi-structured interviews with ten older adults who had a recent ED visit due to a fall. Furthermore, we organised focus groups with 13 healthcare professionals involved in TFCP. Two researchers independently coded the transcripts using inductive thematic analysis. Results We revealed facilitators and barriers on three key themes: 1) Communication, 2) organisation & execution, and 3) personal factors, and thereunder 12 subthemes. Our specific finding were 1a) communication between healthcare professionals and patients, 1b) interprofessional communication and 1c) communication between patients and their family or friends can have both positive and negative impact on the implementation of a TFCP. For the organisation & execution, facilitators and barriers were mentioned for 2a) processes at the ED, 2b) the fall risk assessment, 2c) patient engagement, 2d) finances, 2e) time, and 2f) responsibilities. Personal factors such as 3a) emotions and behaviour, 3b) knowledge, and 3c) motivation play a crucial role in the success of patient participation. The competence of healthcare professionals in geriatric care facilitate the process of tailoring of care to patients' needs. Conclusion When implementing a TFCP, it is crucial to be aware that facilitators and barriers from the perspective of patients and healthcare professionals exist in the processes of communication, organisation & execution, and personal factors. These factors guide the development of tailored implementation strategies in ED and primary care settings.